(Business) Planning for the Future. (1st February 2019) - Fox, Claire
Abstract: This article, by Claire Fox, is designed to share tools and techniques to help with business planning. It will focus on sharing real life knowledge and experience, with practical tips for developing your own business plan. It will lead to a better understanding of why a formal business plan process is crucial to helping teams prepare for the future and remain relevant and necessary to their organisations.